2001
DOI: 10.1093/fampra/18.3.277
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of help-seeking behaviour in older people with unmet needs

Abstract: The majority of older people and their carers do not appear to seek help for their unmet needs for a range of complex reasons, often involving issues of withdrawal, resignation and low expectations. This complexity has implications for the commissioning of services for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 2 publications
3
104
1
Order By: Relevance
“…These ''apparently healthy'' older people are often overlooked within general practice. However, they may fail to seek help or care for their unmet problems or complaints for various reasons (Walters et al 2001). Therefore, this purposive sample might be particularly interesting for GPs as the results of the geriatric assessment might add to their current knowledge of the older person's health and well-being.…”
Section: Selection Of Older Peoplementioning
confidence: 99%
“…These ''apparently healthy'' older people are often overlooked within general practice. However, they may fail to seek help or care for their unmet problems or complaints for various reasons (Walters et al 2001). Therefore, this purposive sample might be particularly interesting for GPs as the results of the geriatric assessment might add to their current knowledge of the older person's health and well-being.…”
Section: Selection Of Older Peoplementioning
confidence: 99%
“…Further, UI is considered to be a social taboo and stigmatizing, which is often another reason for women to not seek healthcare or delay in seeking healthcare services for their UI (Hagglund et al, 2003;Howard & Steggall, 2010). Walters et al (2001) cited that withdrawal, resignation and low expectations were found to be dominant reasons for women not seeking assistance for their UI. Further, Horrocks et al (2004) in a grounded theory study of twenty participants over 65 years old added that reasons for not seeking help for UI were independent management of UI, reactions to incontinence and attitudes to ageing and health.…”
Section: The Marginalization Of Elderly Womenmentioning
confidence: 99%
“…17 A health diary study among older people in rural areas also reported that most symptoms were ignored or managed by responders themselves (that is, selfmedication), and when others are consulted these are most likely to be friends and relatives rather than health professionals. 23 The present findings, however, did not support this view.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…14 Other studies have noted that older people may have a reluctance to seek treatment, 15 for example, due to the 'normalisation' of their symptoms in terms of age, even if these symptoms remain highly disruptive; 16 this has also been termed 'age attribution'. 17 This body of work has contributed to the prevailing view of the stoical older person, who may be less likely than other age groups to seek medical intervention. Separately, it has been suggested that women do not identify their symptoms as relating to CHD, as CHD is viewed as largely a male disease.…”
Section: Introductionmentioning
confidence: 99%